Structural and Electrochemical Properties of the High Ni Content Spinel LiNiMnO4 - Tianyi Li; Kai Chang; Ahmed M. Hashem; Ashraf E. Abdel-Ghany; Rasha S. El-Tawil; Hua Wang; Hazim El-Mounayri; Andres Tovar; Likun Zhu; Christian M. Julien (Electrochem, 2021)
This work presents a contribution to the study of a new Ni-rich spinel cathode material, LiNiMnO4, for Li-ion batteries operating in the 5-V region. The LiNiMnO4 compound was synthesized by a sol-gel method assisted by ethylene diamine tetra-acetic acid (EDTA) as a chelator. Structural analyses carried out by Rietveld refinements and Raman spectroscopy, selected area electron diffraction (SAED) and X-ray photoelectron (XPS) spectroscopy reveal that the product is a composite (LNM@NMO), including non-stoichiometric LiNiMnO4-δ spinel and a secondary Ni6MnO8 cubic phase. Cyclic voltammetry and galvanostatic charge-discharge profiles show similar features to those of LiNi0.5Mn1.5O4 bare. A comparison of the electrochemical performances of 4-V spinel LiMn2O4 and 5-V spinel LiNi0.5Mn1.5O4 with those of LNM@NMO composite demonstrates the long-term cycling stability of this new Ni-rich spinel cathode. Due to the presence of the secondary phase, the LNM@NMO electrode exhibits an initial specific capacity as low as 57 mAh g−1 but shows an excellent electrochemical stability at 1C rate for 1000 cycles with a capacity decay of 2.7 × 10−3 mAh g−1 per cycle.